FAKTOR – FAKTOR YANG MEMPENGARUHI PROFITABILITAS Corresponding author PERBANKAN DI INDONESIA - Y. Widi Kurnia Adityantoro; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
One of the references which used to measure the bank performance business is profitability. The purpose of this research is determine factor – factor influencing banking profitability proxy with Return On Asset (ROA). This research is examine influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operating Expenses and Operating Income (BOPO), Loan Deposit Ratio (LDR), Net Interest Margin (NIM), firm size, company status which Listed or not listed on the stock exchange to ROA. This research used purposive sampling method for taking samples. The scope of the research to include all of public private national bank foreign exchange and not foreign exchange which provide financial report during period 2009 through 2011. Data obtained on the basis of publication Annual Bank, obtained 43 samples of General Bank. Analysis technique used in this research is multiple linear regression analysis. The results of this research found that Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operating Expenses and Operating Income (BOPO), and Loan Deposit Ratio (LDR), have significant influence to ROA. While Net Interest Margin (NIM), firm size, and Listed doesn’t have influence to ROA.